Biological characteristics of a human population from Lusatian Culture period exploiting burial ground at Bruszczewo (Poznań voivodeship) - Piontek, Janusz; Marecki, Bogusław; Berdychowski, Włodzimierz (Anthropological Review, 1980)
The paper presents results of anthropological examination of 254 burial units. Skeletal remains of 270 individuals were distinguished (thus some graves contained remnants of more than one individual) and their sex and age at death ostimated. Mortality parameters were reconstructed directly from the data (see life table 1.), then after correcting for underestimation of deceased children from skeletal material (table 2), and finaly after correcting for assumed a priori rate of natural increase (0.004 per year) — see table 3. For calculating probable frequency of subadults deaths a method proposed by M. Henneberg (1977) was employed. Biological state and dynamics of a group in question have been estimated by means of analysing the group's adaptation to selective factors. To this end a potential gross reproductive rate has been computed (Root) This measure informs what part of total fertility rate had been realised by an average pair of parents in a population (table 4). Another measure serying the same purpose — the Biological State Index (Ibs) has also been computed. Its values for the group in question indicate that a probability for full participation in reproduction for an average individual born in the group was 0.31 - 0.34 (0.34 is the index value for reproductive structure corrected for assumed natural increase rate). Methods of calculation and interpretation of the aforedescribed indices are given in M. Henneberg [1975] and M. Henneberg & J. Piontek [1975]. Tables 5 & 6 contain information on reconstructed living population structure by age, based on assumed stationary population state and stable state with positive naural increase. In the age structure more than 20% had been constituted by children requiring care from other members of the group, 44% consisted of adults capable to conduct productive tasks whrereas 6% of the group consisted of elders. In some burials epiphyses of long bones were exceptionally well preserved enabling thus measurements to be taken (see table 7). On grounds of these measurements body height was reconstructed by methods elaborated by Strzalko et al. (1972)— see table 8. Results of the present study allow one to conclude the following: 1. The population in question was characterized by moderate potential for reproduction, under assumption of non-Malthusian fertility. Therefore the population had capability for natural increase at a rate of several individuals per thousand per year. 2. Frequency of subadult remains found at the burial ground is too low in comparison with expected value. Estimation of probable frequency of subadult deaths is particularly important for reasonable reconstruction of living population structure and of size of nuclear family. 3. The group examined does not differ in important characteristics of adult mortality from other human populations living in Central Europe during Bronze Age.